Oral Lesions Induced by Chronic Khat Use Consist Essentially of Thickened Hyperkeratinized Epithelium - Ochiba Mohammed Lukandu; Lionel Sang Koech; Paul Ngugi Kiarie (International Journal of Dentistry)
Objectives. The habit of khat chewing is prevalent in many Middle Eastern and African cultures and has been associated with various adverse conditions in humans. This study aimed to describe histological changes induced by chronic khat chewing on the buccal mucosa. Methods. Biopsies of the buccal mucosa from 14 chronic khat chewers, 20 chronic khat chewers who also smoked tobacco, and 8 nonchewers were compared for epithelial thickness, degree and type of keratinization, and connective tissue changes. Results. Tissues from khat chewers depicted abnormal keratinization of the superficial cell layer and showed increased epithelial thickness affecting all layers. Epithelial thickness in control samples was 205 ± 26 μm whereas thickness in khat chewers and khat chewers who smoked tobacco was significantly higher measuring 330 ± 35 μm and 335 ± 19 μm, respectively. Tissues from khat chewers also showed increased intracellular edema, increased melanin pigment deposits, and increased number of rete pegs most of which were thin and deep. Conclusions. These results show that oral lesions induced by chronic chewing of khat in the buccal mucosa present with white and brown discoloration due to increased epithelial thickness, increased keratinization, and melanin deposition.